2021
DOI: 10.1016/j.jbc.2021.101011
|View full text |Cite
|
Sign up to set email alerts
|

GH18 endo-β-N-acetylglucosaminidases use distinct mechanisms to process hybrid-type N-linked glycans

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Even when bound in the glycan binding sites of endoglycosidases that are not protein-specific, N-linked glycans adopt diverse structures that are decidedly unlike the parallel-branched glycans in EndoS and EndoS2. This is the case for the N-linked glycans that are the substrates for EndoBT-3987 38,39 (Supplementary Fig. 34), EndoF 3 40 , as well as many others.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Even when bound in the glycan binding sites of endoglycosidases that are not protein-specific, N-linked glycans adopt diverse structures that are decidedly unlike the parallel-branched glycans in EndoS and EndoS2. This is the case for the N-linked glycans that are the substrates for EndoBT-3987 38,39 (Supplementary Fig. 34), EndoF 3 40 , as well as many others.…”
Section: Discussionmentioning
confidence: 87%
“…We also studied the interaction of catalytically-inactive EndoBT-3987 D312A/E314 , a GH18 family ENGase that hydrolyzes HM glycans from myriad glycoproteins but is not specific for IgG antibodies or any other protein (Supplementary Fig. 16) 38,39 . Quantitative lineshape analysis of methyl-TROSY spectra showed that EndoS2 D186L binds Rituximab-Fc with a dissociation constant of 3.1 µM (Table 1, entry 1), similar to the previously reported K D of ∼9 µM for the binding of EndoS2 D186L to IgG1-CT obtained by surface plasmon resonance 28 .…”
Section: Igg Glycoprotein Substratesmentioning
confidence: 99%
“…Even when bound in the glycan binding sites of endoglycosidases that are not protein-specific, N -linked glycans adopt diverse structures that are decidedly unlike the parallel-branched glycans in EndoS and EndoS2. This is the case for the N -linked glycans that are the substrates for EndoBT-3987 42 , 43 , EndoF 3 44 , as well as many others (Supplementary Fig. 35 ).…”
Section: Discussionmentioning
confidence: 88%
“…We also studied the interaction of catalytically inactive EndoBT-3987 D312A/E314L , a GH18 family ENGase that hydrolyzes HM glycans from myriad glycoproteins but is not specific for IgG antibodies or any other protein (Supplementary Fig. 17 ) 42 , 43 . Quantitative line shape analysis of methyl-TROSY spectra showed that EndoS2 D186L binds Rituximab-Fc with a dissociation constant of 3.1 µM (Table 1 , entry 1), similar to the previously reported K D of ∼9 μM for the binding of EndoS2 D186L to IgG1-CT obtained by surface plasmon resonance 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Research into the structure–function relationship for GH18 enzymes that hydrolyse N-glycans from a number of different species has made huge progress over the last few years ( Figure 5 ). This is largely due to solving new product–complex crystal structures but also scanning mutagenesis to understand the contribution of the different residues in the active sites [ 22 , 25 , 26 ]. A number of observations and trends are emerging from the comparison of structural data of different enzymes.…”
Section: Cazymes That Liberate N-glycans From Glycopeptidesmentioning
confidence: 99%